Preschool life skills: Recent advancements and future directions. Issue 1 (8th January 2018) - Fahmie, Tara A.; Luczynski, Kevin C.
Abstract : Over the past decade, researchers have replicated and extended research on the preschool life skills (PLS) program developed by Hanley, Heal, Tiger, and Ingvarsson (2007). This review summarizes recent research with respect to maximizing skill acquisition, improving generality, evaluating feasibility and acceptability, and testing predictions of the initial PLS study. For each area, we suggest directions for future research.